Role of the aclacinomycin A--doxorubicin association in reversal of doxorubicin resistance in K562 tumour cells. - Millot, J. M. (Nature Publishing Group, 1989)
Acquired resistance to anthracyclines is characterised by a lower sensitivity to these agents, associated with impaired accumulation of drug. We have examined the ability of aclacinomycin A (ACM) associated with doxorubicin (DOX), to increase intranuclear DOX concentrations and, consequently, to enhance cytotoxic effects against drug resistant cells in vitro. A recently developed microspectrofluorometric technique is used to measure intranuclear DOX concentrations in sensitive and DOX-resistant K562 cells treated with DOX and ACM. Fluorescence emission spectra are collected from a microvolume of single living cell nuclei. From both DOX and ACM model fluorescence spectra (free, DNA-bound and metabolites), the intranuclear spectral profile is analysed according to the amount of each component. This quantitative analysis determines intranuclear DOX concentrations with an error of 10%. Non-cytotoxic doses of ACM, in combination with DOX, increase cytotoxic activity of DOX against K562 resistant cells. When DOX-resistant cells are exposed simultaneously to ACM and DOX, significant increases in intranuclear DOX concentrations are found compared with the case of exposure to DOX alone. The measure of the intranuclear retention of DOX shows that ACM partly blocks the DOX efflux in resistant cell nuclei, resulting in enhanced accumulation of DOX. These data lead us to conclude that ACM-DOX association partly reverses the DOX resistance at clinically achievable concentrations.